Factores de riesgo y cuadro clínico de dengue en pacientes atendidos en el Hospital básico Macará - Encalada Valdivieso, Angela Carolina (2023)
Dengue is one of the diseases transmitted by the bite of a mosquito infected with one of the four serotypes of the dengue virus, affecting both children and adults. The purpose of this study was to determine the risk factors and clinical picture of dengue in patients treated at Macará basic hospital from March 2020 to June 2021, according to sex, age group and place of residence. A descriptive, quantitative, observational, cross-sectional, retro prospective study was applied, with a sample of 78 people diagnosed with dengue. The following results were obtained: the highest number of dengue cases was found in the 15-49 years age group with 55.17%, being more prevalent in the female sex with 55.17% (n=32). The most prevalent clinical picture was dengue with signs of alarm in 75.6% (n=59), related to the place of residence. Among the main risk factors: the presence of mosquitoes in the area with 56.4% (n=44), the presence of mosquitoes in the house with 72% (n=56), the presence of flower vases inside the house with 69.2% (n=54), the presence of empty bottles in the yard with 59% (n=46) and as a main risk factor we have the use of tires to support the zinc roof of the houses 94.9% (n=74). It was found that there is a statistically significant relationship (x2= 8.754 gl= 1 p=0.0003) between the presence of flower vases inside the house and the clinical picture for contracting dengue.